ANALYSIS OF THE ROLE OF MARKETING DIGITALIZATION ON EASE OF DIGITAL TRANSACTIONS (CASE STUDY OF KAF'S DORAYAKI MSMES) - Septyarina Hastin Wulandari; Siti Saroh; Khoiriyah Trianti (International Journal of Entrepreneur and Business Administration, 2023)
The results of this study show that in the implementation of digital marketing for UMKM Kaf's Dorayaki, the strategy of utilizing marketing platforms such as Instagram, Shopee, GrabFood and GoFood has proven a crucial role in expanding the market and facilitating transactions. Even though MSME owners are aware of the benefits and potential of digitalization, there are challenges such as optimizing platform features that have not been fully realized. In addition, the role of marketing digitalization in product information dissemination, service improvement, and market research also has a positive impact on customer awareness and positive brand perception. However, aspects such as clear presentation of information and a professional visual appearance still need to be improved. Convenience constructs such as "easy to learn", "controllable", "clear and understandable", "flexible", "easy to become skillful", and "easy to use" in the context of using Instagram as an effective marketing tool have helped in achieve business goals more efficiently.